Prevalence and Determinant Analysis of Scabies Incidence in Rumak Village - Halid, Idham; Halid, Musparlin; Binarto Budi Susilo, Beny (Universitas Nahdlatul Ulama Surabaya, 2024)
Scabies is a global public health problem that affects millions of people worldwide, especially in crowded and underdeveloped places. Similar difficulties arise at Rumak Village, a rural community in West Lombok, where cramped living quarters encourage the development of scabies. The primary goal of this research is to pinpoint the critical factors affecting the village's scabies transmission. Using a cross-sectional methodology, 483 families' preventive practices were investigated between January and July of 2023. Chi-Square tests were used to analyse the data, which were gathered by questionnaires. A p-value threshold of 0.05 and a 95% confidence interval were used for the analysis. The results showed a substantial correlation (p = 0.000) between the occurrence of scabies and poor handwashing habits, poor household cleanliness, sharing personal objects, and infrequent bathing. Scabies is more common in families who bathe only once a day, interchange personal belongings regularly, have dirty surroundings, and wash their hands infrequently.